Commentary on "Empowering caregivers of children with learning and developmental disabilities: from situation analysis to community-based inclusive development in Kilifi, Kenya". Issue 1 (7th March 2022) - Leadbitter, Kathy; Divan, Gauri
Abstract : Purpose: This paper is a commentary which aims to address themes arising from the article by Bunning et al. entitled "Empowering caregivers of children with learning and developmental disabilities: from situation analysis to community-based inclusive development in Kilifi, Kenya". Design/methodology/approach: This commentary provides discussion stimulated by the paper by Bunning et al., including important areas for consideration when developing and evaluating care pathways or solutions to providing support to families of children with disabilities in low- and middle-income countries. Findings: This commentary highlights issues such as: the value of transported and home-grown approaches; the importance of empowerment and advocacy; and the benefits of equitable collaborative partnerships between researchers in low- and middle-income countries and those in high-income countries. Originality/value: This is the personal perspective of two collaborators who have been working in the field of service delivery of complex interventions for children with developmental disabilities in high- and low-income country settings.